Cardiovascular and respiratory responses during graded exercise in adolescents after sport-related concussion - Leddy, J. J.; Haider, M. N.; Chizuk, H. M.; Nazir, M. S. Z.; Worts, P.; Willer, B. S.; Johnson, B. D. (Sports Medicine, 2026)
Background: Symptom-limited exercise intolerance is a physiological sign of sport-related concussion. Possible etiologies include rest-induced aerobic deconditioning and/or impaired cardiopulmonary function. Objective: This study examined cardiovascular and respiratory function at rest and during progressive cycle ergometer exercise in adolescents within 10 days of sport-related concussion compared with non-concussed athletes. Methods: Concussed participants (n = 26, 15.4 ± 1.1 years, 54% male, 7.3 ± 1.8 days from injury) and control participants (n = 24, 15.8 ± 1.6 years, 58% male) performed the Buffalo Concussion Bike Test. Blood pressure, heart rate, stroke volume, cardiac output, respiratory rate, minute ventilation, oxygen consumption, and end-tidal CO2 were collected at rest and continuously during exercise. Results: Concussed participants exercised for 16.24 ± 5.6 min, experienced a greater than 2-point (on a 0-10 scale) exacerbation of their concussion symptoms at their final minute, and reported higher perceived exertion throughout exercise versus controls. Controls exercised for 25.08 ± 7.0 min up to voluntary exhaustion without reporting any concussion-like symptoms. Concussed participants` cardiovascular and respiratory parameters did not differ at rest versus controls, but concussed participants had higher minute ventilation and their blood pressure plateaued at lower values during the first 10 min of exercise. Conclusions: No evidence of aerobic deconditioning was found within 10 days of injury. Our study found attenuated cardiopulmonary responses to progressive aerobic exercise, which may be a cause for exercise intolerance in concussed adolescent athletes. Additional research is warranted to determine if this may be related to altered autonomic nervous system regulation.